Antimicrobial activities of ethanol extract from leaf of plectranthus amboinicus / Nor Aainaa Athirrah Mohd - Mohd, Nor Aainaa Athirrah (Faculty of Applied Sciences, 2016)
Plectranthus amboinicus are belongs to the family Lamiaceae, or bestly known as motherland plant in English. It may be an extensive youthful herb, with exceedingly scented, branched, possessing short delicate erect hairs for dissimilar inhaling abandons. The compound that are found in any part of the plant Plectranthus amboinicus from extraction proces is beneficial and can be used as antibiotic to fight against pathogens. The broad use and misuse of antibiotics led to the rise of drugs that are opposed to bacterial and fungal. So it is fundamental to find on alternate to antibiotics. Study was conducted to investigate the antimicrobial potential of ethanol extract of leaf of Plectranthus amboinicus against selected bacteria and to compare the two antimicrobial assay by using disc diffusion method and minimum inhibitory concentration method. The study of medicinal properties crude extract prepared using solvent such as ethanol were subjected to antimicrobial activity using Kirby-Bauer disk diffusion method. The verification for minimum inhibitory concentration (MIC) was verify using dilution method against various clinical pathogens like Escherichia coli, Salmonella typhimurium, Bacillus subtilis and Staphylococcus aureus. After 24 hours incubation, the zone of inhibition was measured and compared with standard antibiotics gentamycin (1 0μg/disc ). Mostly at concentration 100 mg/ml the extract found to be more effective against Gram-positive bacteria compared to Gramnegative bacteria. Escherichia coli found to be least susceptible with 7mm diameter at concentration 100 mg/ml. Wherease, Bacillus subtilis found to be the most susceptible bacterium with 13.2mm diamter at concentration 1 00mg/ml towards the ethanol extract. The minimum inhibitory concentration (MIC) of. B.subtilis recorded were 0.20mg/ml, E.coli were 6.25 mg/ml, S.typhi were 3.13 mg/ml and S.aureus were 1.56mg/ml. The results showed that the plant has significant differeces (pS0.05) at concentration 1 00mg/ml. From the data clearly shows that the ethanol extract of Plectranthus amboinicus has the ability to possess powerful inhibitory towards all the pathogenic microorganisms. Increase the concentration is best recommended for upcoming studies of antimicrobial activity of the plant Plectranthus ambonicus.